2005
DOI: 10.1038/nm1216
|View full text |Cite
|
Sign up to set email alerts
|

Can successful vaccines teach us how to induce efficient protective immune responses?

Abstract: Some recently introduced vaccines that have excellent efficacy records have been developed without a clear understanding of their mechanism of protection. In fact, successful vaccines have often emerged out of empirical observations and have only rarely been the result of a rational use of the continuously increasing immunological knowledge available to scientists. However, a posteriori deciphering of the biological bases for the efficacy of successful vaccines should be an essential component of research effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
102
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(108 citation statements)
references
References 77 publications
(77 reference statements)
2
102
1
3
Order By: Relevance
“…We could confirm this finding in that the neutralizing and binding titers were the highest in those individuals who were in their first decade of life during the period of time when the corresponding subtype was circulating. Older individuals also had significantly more binding and neutralizing antibodies against old than against more recent isolates (eg, H3/99; Supplementary Figure 2), which may reflect original antigenic sin [17]. In contrast, in line with other studies [18], we found antibody titers to the last prestudy isolates (2007) to be the same in all age groups.…”
Section: Discussionsupporting
confidence: 88%
“…We could confirm this finding in that the neutralizing and binding titers were the highest in those individuals who were in their first decade of life during the period of time when the corresponding subtype was circulating. Older individuals also had significantly more binding and neutralizing antibodies against old than against more recent isolates (eg, H3/99; Supplementary Figure 2), which may reflect original antigenic sin [17]. In contrast, in line with other studies [18], we found antibody titers to the last prestudy isolates (2007) to be the same in all age groups.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the limitations of the immune system in early life, successful pediatric vaccines exist. Deciphering the biological basis for their efficacy will be useful for developing optimal vaccination strategies to protect the very young [54].…”
Section: Discussionmentioning
confidence: 99%
“…However, the animals inoculated with purified PCV2 should not constitute a control group to assess the candidate vaccine, given that the imunization with purified inactivated virus is direct antigen application (Lambert et al 2005), whereas the DNA vaccination assay is an in vivo transfection assay (Babiuk et al 2003). Sera of these animals were produced only for ELISA standardization.…”
Section: Discussionmentioning
confidence: 99%